2004
DOI: 10.1016/s0378-1097(04)00068-0
|View full text |Cite
|
Sign up to set email alerts
|

Essential residues in the chromate transporter ChrA ofPseudomonas aeruginosa

Abstract: The chrA gene of Pseudomonas aeruginosa plasmid pUM505 encodes the hydrophobic protein ChrA, which confers resistance to chromate by the energy-dependent efflux of chromate ions. Chromate-sensitive mutants were isolated by in vivo random mutagenesis. Transport experiments with cell suspensions of selected mutants showed that 51CrO4(2-) extrusion was drastically lowered as compared to suspensions of the strain with the wild-type plasmid, confirming that the mutations affected a chromate efflux system. DNA seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 22 publications
6
23
0
2
Order By: Relevance
“…Random mutagenesis of the P. aeruginosa chrA gene showed that most essential amino acid residues are located in the amino terminal end of ChrA (Aguilera et al 2004). In agreement with this finding, phylogenetic analysis of ChrA homologs revealed that the amino terminal halves are more conserved than the carboxyl terminal halves (Díaz-Pérez et al submitted).…”
Section: Transmembrane Efflux Of Chromatementioning
confidence: 99%
“…Random mutagenesis of the P. aeruginosa chrA gene showed that most essential amino acid residues are located in the amino terminal end of ChrA (Aguilera et al 2004). In agreement with this finding, phylogenetic analysis of ChrA homologs revealed that the amino terminal halves are more conserved than the carboxyl terminal halves (Díaz-Pérez et al submitted).…”
Section: Transmembrane Efflux Of Chromatementioning
confidence: 99%
“…Recently, a series of random mutant strains isolated as chromate sensitive identified 14 residue positions (of the 416 amino acids in ChrA) that are needed for chromate resistance. The positions affected seemed mostly in the N-terminal half of the protein and occurred both in the membrane segments and cytoplasmic loop regions [1].…”
Section: Other Metal Resistancesmentioning
confidence: 99%
“…However, there is little sequence similarity (35% similarity across 106 of 225 amino acids) between the amino and carboxy halves of Arth_4248; hence, it does not appear to have arisen by direct tandem duplication of the same CHR domain-containing open reading frame. Because of the topological diversity of the CHR superfamily proteins [22,25] and the observed preponderance of conserved residues in the N-terminal half of the P. aeruginosa ChrA protein [26], it is expected that the amino and carboxy termini may carry out different functional roles in chromate efflux. Alignment of the amino acid sequence of Arth_4248 with that of P. aeruginosa ChrA indicated that residues which resulted in Cr(VI) sensitivity following mutation in P. aeruginosa [26] are also conserved in Arth_4248.…”
Section: Resultsmentioning
confidence: 99%